Receptor interaction profiles of 4-alkoxy-2,6-dimethoxyphenethylamines (Ψ derivatives) and related amphetamines - Kolaczynska, Karolina E.; Trachsel, Daniel; Hoener, Marius C.; Liechti, Matthias E.; Luethi, Dino (Frontiers in Pharmacology, 2025)
Background4-substituted 2,6-dimethoxyphenethylamines and the corresponding amphetamines (so-called pseudo [Ψ] derivatives) are a hitherto mostly unexplored group of psychedelics. Still, preliminary investigations indicate that these derivatives are promising and potent psychedelics in humans. In this study, we examined the monoamine receptor and transporter interaction properties of several 4-alkyloxy-2,6-dimethoxyphenethylamines and amphetamines with varying structural modifications at the 4-alkyloxy position and compared them to structural analogs with 3,4,5- and 2,4,5-substitution patterns.MethodsBinding affinities were assessed at human serotonergic 5-HT1A, 5-HT2A, and 5-HT2C receptors, adrenergic α1A and α2A receptors, dopaminergic D2 receptor, rat and mouse trace-amine associated receptor 1 (TAAR1), and human monoamine transporters. Moreover, the Ψ derivatives were examined for their activation potency at human 5-HT2A and 5-HT2B receptors and at human TAAR1.ResultsThe tested derivatives displayed moderate to high affinity and activity at the h5-HT2A receptor (Ki = 8–1,600 nM; EC50 = 32–3,400 nM). All derivatives were partial agonists at the receptor (activation efficacy ≤84%). Moreover, the phenethylamine derivatives bound to the h5-HT1A (Ki = 710–4,440 nM) and h5-HT2C (Ki = 110–3,500 nM) receptors with moderate affinity, whereas the amphetamine derivatives showed weak h5-HT1A affinities (Ki ≥ 5,100 nM) and comparably lower h5-HT2C receptor affinities (Ki = 270–10,000 nM). Within the remaining receptors investigated, some of the Ψ derivatives showed significant interactions with the human (EC50 ≥ 34 nM), rat (Ki ≥ 1.6 nM), and mouse (Ki ≥ 120 nM) TAAR1, the hα1A adrenoceptor (Ki ≥ 670 nM) and the hα2A adrenoceptor (Ki ≥ 280 nM).ConclusionThe Ψ derivatives mainly interacted with the 5-HT2A receptor, the primary target for psychedelics, as well as with the 5-HT2C receptor. The same 4-alkyloxy modification pattern on the related 2,4,5-trisubstituted derivatives exhibited generally slightly more potent 5-HT2A receptor binding and activation, whereas 3,4,5-trisubstituted derivatives interacted with lower potency; in humans, 2,4,6-trisubstituted derivatives may thus be less potent compared to their 2,4,5-trisubsititued counterparts but more potent compared to their 3,4,5-trisubsititued counterparts.